The time-sharing contract between jurisprudence and law: A comparative study - Alobaid, Sami Ahmed; Alnajjar, Yasir AbdulHamid (Journal of Humanities & Social Sciences, 2022)
Within the framework of economic activity, transactions appeared that took a space between members of society, and the most important characteristic of this system is that it mixed the element of place, which is the real estate unit, and the element of time represented by the time unit, which enables the beneficiary to benefit during the year and over the years, and the beneficiary does not benefit from the whole year, but alternates with the rest. In the light of division, and the problem of the study in achieving a perception of the economic contract adaptation; This study will depend on the inductive approach by collecting data, then processing, analyzing, categorizing and then summarizing them with the addition of the ideas that were drawn, to arrive at an interpretation of the method, based on the legal and regulatory evidence. The time- sharing contract aimed to involve the largest number of people at the lowest cost, and how Sharia and the system dealt with its violations, and to establish legal formulas. The results can be summed up that the contract aims at greater benefit and participation for the participants. The contract has two forms, and it is presented in the form of a sale contract... and it takes either the form of the lease contract or the form of a contract establishing a usufruct right. This contract is based on three pillars: satisfaction, place and reason. The general rules of jurisprudence and law are not valid, whether those related to the sale contract or the lease contract by conformity. The place of the contract is the real estate unit and the time that is distinguished by it. This contract consists of characteristics, as it is a netting contract.. Among the recommendations is the necessity of issuing Islamic legislation related to regulating the contract, and tightening control over companies that work in this field.
Keywords: time sharing; time